2011
DOI: 10.1111/j.1440-1797.2011.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of betel nut chewing with chronic kidney disease: A retrospective 7‐year study in Taiwan

Abstract: The association between BN chewing and CKD seemed conditional on demographics, health behaviours, and underlying co-morbidities. This association should be interpreted cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Second, we used gender-stratified analysis to document the different effects of alcohol drinking on CKD in men and women. In addition, previous research indicated that anemia, hyperuricemia, and BN chewing were associated with CKD [20,38-40], so we adjusted for these confounders in our multivariable analysis. Besides, we conducted a series of sensitivity tests to remove impacts of reverse causality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we used gender-stratified analysis to document the different effects of alcohol drinking on CKD in men and women. In addition, previous research indicated that anemia, hyperuricemia, and BN chewing were associated with CKD [20,38-40], so we adjusted for these confounders in our multivariable analysis. Besides, we conducted a series of sensitivity tests to remove impacts of reverse causality.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed description and definitions of variables in the dataset were described previously [20]. Briefly, from 2003 to 2009, 34 372 people who attended a national health insurance sponsored health check-up program in Ditmanson Medical Foundation Chia-Yi Christian Hospital, were selected as study subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the rate of betel nut consumption, other than through education and health promotion programmes, strategies have been devised to encourage physical activity and oral hygiene 17. Another strategy includes fines and mandatory withdrawal classes for those who spit in public 18. According to another study, an effective approach would be to apply taxes on wholesalers who are easily identifiable and who make the greatest profit from the industry 2.…”
Section: Bioethical Reflectionsmentioning
confidence: 99%
“…A higher rate of concurrent usage of oral substances, particularly in the CKD group, indicates certain lifestyle patterns, which may confer a higher health risk [41]. However, previous studies demonstrated an inverse association between alcohol consumption and renal dysfunction [42], [43] because beneficial oxidative activity on endothelial function has a protective property for kidneys [42], [44]. Additionally, in Taiwan, CKD prevalence among betel-nut users is higher than in the non-users in all age groups [43].…”
Section: Discussionmentioning
confidence: 99%